2020
DOI: 10.1038/s41598-020-62886-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals differentially expressed genes associated with high rates of egg production in chicken hypothalamic-pituitary-ovarian axis

Abstract: The hypothalamic-pituitary-ovarian (HPO) axis regulates the breeding process cycle of laying hens. However, the key regulatory genes of the HPO axis and pathways that drive chicken egg laying performance remain elusive. A total of 856 Chinese Luhua chicken was raised and the highest two hundred and the lowest two hundred chicken egg production were considered as high egg production (HEP) and low egg production (LEP) according to the total egg number at 300 days of age, respectively. RNA-seq sequencing (RNA-Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 33 publications
3
53
2
Order By: Relevance
“…Recent studies have shown that the follicular development and granulosa cell survival and proliferation can be improved by regulating the expression of PI3K/Akt signaling pathway [ 65 ]. Mishra et al (2020) found that DEGs associated with high rates of egg production regulate PI3K-Akt signaling pathway at hypothalamic-pituitary-ovarian axis in laying hens [ 66 ]. The ovaries with reproductive activity are composed of small pre-hierarchical and maturing preovulatory follicles showing a hierarchy according to their size [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the follicular development and granulosa cell survival and proliferation can be improved by regulating the expression of PI3K/Akt signaling pathway [ 65 ]. Mishra et al (2020) found that DEGs associated with high rates of egg production regulate PI3K-Akt signaling pathway at hypothalamic-pituitary-ovarian axis in laying hens [ 66 ]. The ovaries with reproductive activity are composed of small pre-hierarchical and maturing preovulatory follicles showing a hierarchy according to their size [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are five differentially expressed genes (DEGs) that were identified in the ovaries of Jinghai Yellow chickens related to egg production including ZP2 , WNT4 , AMH , IGF1 , and CYP17A1 , which serve as potential candidate genes for improving egg production ( Zhang et al, 2019 ). It was reported that 414, 356, and 10 DEGs from the hypothalamus, pituitary gland, and ovary, respectively, of the Chinese domestic Luhua chicken were potentially associated with greater rates of egg production ( Mishra et al, 2020 ). These results provided valuable information for understanding the reproductive biology of chicken and identifying effective molecular markers for genetic improvement of the domestic chicken breed.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the genetic potential of chickens is one of the most important strategies utilized to increase egg production. However, conventional breeding techniques, that are based on long-term selections using egg number and laying rate, are usually laborious and time consuming [2]. Currently, various high-throughput techniques that can identify genes at the genomic and transcriptomic levels have been increasingly employed when studying poultry reproduction.…”
Section: Introductionmentioning
confidence: 99%